Penguatan Pendidikan Karakter Melalui Pendidikan Agama - Maulana, Rini; Asy’ari, Muhammad Hasanil (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2025)
The purpose of this study is to see what kind of character reinforcement can build student character based on Islamic values. This research uses descriptive qualitative research in the field by using observation, interview, group discussion (FGD) data collection techniques and documentation. In addition, data is presented using a descriptive approach, in the form of words, writing, to clarify the data collected and analyzed. The results of the study show that strengthening character education through Islamic education in SMPIT DARUL MUHSIN is divided into 3 fields: class-based KDP, school-based KDP, community-based KDP can be said to be good and not. Class-based KDP has been done well at SMP 3 Bandar Lampung because each stage has been done well. These stages include integrating KDP into the program, KDP through classroom management, KDP through the choice and use of thematic learning methods, KDP by the literature movement, KDP through guidance and counseling. Of the five stages of implementation, it can be said that it is maximized and implemented well. The next field is school culture based on KDP. In school culture, many core KDP values are applied. KDP based on school culture in its implementation went well. The socio-cultural conditions in SMPIT DARUL MUHSINare very easy to implement, for various types of noble values, so that examples of education can be easily integrated with students. Community-based KDP in its implementation in SMPIT DARUL MUHSIN has not worked in accordance with the KDP concept itself. This is due to the limited scope of its implementation. However, some things can be implemented, including social relations between school committees and parents as key actors in education. There is still limited collaboration, namely the ulama community and the teacher of the Koran. Therefore it can be concluded that among the three KDP fields that have not been properly implemented, it is community based KDP